A Dynamic Chemical Network for Cystinuria Diagnosis. Issue 28 (20th April 2018) - Lafuente, Maria; Solà, Jordi; Alfonso, Ignacio
Abstract: The study of molecular networks represents a conceptual revolution in chemistry. Building on previous knowledge and after understanding the rules of non‐covalent interactions, the design of stimulus‐responsive chemical systems is possible. Herein we report a new strategy, based on the reorganization of a dynamic chemical network that generates new fluorescent associations in the presence of cysteine or cystine. The binding and sensing units are encoded in the components that dynamically assemble and disassemble responding to external stimuli as a successful tool to detect both cysteine and cystine in aqueous media. Moreover, the dynamic sensing system works in human urine, as a prospective application for cystinuria diagnosis. Abstract : Cystine system : A dynamic covalent chemical system rearranges in the presence of cysteine and cystine to give a fluorescent signal. The chemical system can be used to detect pathological amounts of the biothiol in urine.